Complex and prolonged hypercoagulability in coronavirus disease 2019 intensive care unit patients: A thromboelastographic study. Issue 2 (March 2021) - Cordier, Pierre-Yves; Pierrou, Candice; Noel, Alexandre; Paris, Raphaël; Gaudray, Eliott; Martin, Edouard; Contargyris, Claire; Bélot-De Saint Léger, Frédérik; Lyochon, Arthur; Astier, Hélène; Desmots, Florian; Savini, Hélène; et al.
Abstract: Background: A high number of thrombotic complications have been reported in critically ill patients with coronavirus disease 2019 (COVID-19) and appear to be related to a hypercoagulable state. Evidence regarding detection, management, and monitoring of COVID-19–associated coagulopathy is still missing. We propose to describe the thrombus viscoelastic properties to investigate the mechanisms of hypercoagulability in patients with COVID-19. Methods: Thromboelastography (TEG) was performed in 24 consecutive patients admitted to a single intensive care unit for COVID-19 pneumonia, and 10 had a second TEG before being discharged alive from the intensive care unit. Results: Compared with a group of 20 healthy participants, patients with COVID-19 had significantly decreased values of reaction time, coagulation time, and lysis index and increased values of α angle, maximum amplitude, clot strength, and coagulation index. Velocity curves were consistent with increased generation of thrombin. These values persisted in surviving patients despite their good clinical course. Discussion: In patients with COVID-19, TEG demonstrates a complex and prolonged hypercoagulable state including fast initiation of coagulation and clot reinforcement, low fibrinolysis, high potential of thrombin generation, and high fibrinogen and platelet contribution. The antithrombotic strategy in patients with COVID-19 during intensive care hospitalisation and after discharge should be investigated in further studies.